The Effectiveness of Intravesical Oxybutynin, Propantheline, and Capsaicin in the Management of Neuropathic Bladder following Spinal Cord Injury - Jacob George; George Tharion; J. Richar; Ashish S. Macaden; Raji Thomas; Suranjan Bhattacharji (The Scientific World Journal)
The objective of this study was to compare the therapeutic response of intravesical oxybutynin, propantheline, and capsaicin in the treatment of neurogenic detrusor overactivity. Carried out in the Department of Physical Medicine and Rehabilitation at a university teaching hospital in India, patients acted as their own controls. Oxybutynin 5 mg in solution or propantheline 15 mg in solution and capsaicin were instilled intravesically in each patient. Urodynamic studies were done before and after the intravesical instillation of each drug. The nonparametric tests were used for statistical analysis. The efficacy of intravesical capsaicin in the treatment of neurogenic detrusor overactivity was statistically significant for reflex volume (RV) (p = 0.018), cystometric capacity (CC) (p = 0.0440), leak volume (LV) (p = 0.000), and leak frequency (LF) (p = 0.009). The Kruskal-Wallis test for paired sample comparing pre- and post-LV and LF for intravesical capsaicin was significant at 2nd week (p = 0.002 and 0.054, respectively). There was a significant difference in therapeutic response between intravesical oxybutynin, propantheline, and capsaicin in the treatment of detrusor overactivity for LV and LF at 2nd week (p = 0.017 and 0.003, respectively). When comparing responses of oxybutynin and propantheline, more subjects demonstrated improvement with intravesical propantheline than oxybutynin for RV, detrusor leak point pressure (LPP), clean intermittent catheterization volume (CICV), and LV. This study suggests that intravesical agents may be used as effective adjuvants in the management of incontinence due to neurogenic detrusor overactivity following spinal cord injury.